2017
DOI: 10.1038/s41598-017-17152-0
|View full text |Cite
|
Sign up to set email alerts
|

Fisheries-independent surveys identify critical habitats for young scalloped hammerhead sharks (Sphyrna lewini) in the Rewa Delta, Fiji

Abstract: Sharp declines in numerous shark populations around the world have generated considerable interest in better understanding and characterising their biology, ecology and critical habitats. The scalloped hammerhead shark (SHS, Sphyrna lewini) is subject to a multitude of natural and anthropogenic threats that are often exacerbated within the coastal embayments and estuaries used during SHS early life stages. In this study, we describe the temporal and spatial distribution, age class composition, and reproductive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 62 publications
1
33
0
Order By: Relevance
“…These results suggest that the parturition period in Fiji's southern riverine systems occurs during the wet austral summer season, with a possible peak between December and January. This is in line with Cardeñosa et al (), who reported that bull shark sightings or catches by fishers in Fiji mainly occur during summer, and also largely overlap with the characterization of other shark species' parturition season in Fiji (Marie et al, ; Vierus et al, ). Furthermore, parturition occurring in the austral summer corresponds with direct observations made in the SRMR where pregnant bull sharks leave the feeding site in late October, returning after parturition at the beginning of the year (Brunnschweiler et al, ; Brunnschweiler & Baensch, ).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…These results suggest that the parturition period in Fiji's southern riverine systems occurs during the wet austral summer season, with a possible peak between December and January. This is in line with Cardeñosa et al (), who reported that bull shark sightings or catches by fishers in Fiji mainly occur during summer, and also largely overlap with the characterization of other shark species' parturition season in Fiji (Marie et al, ; Vierus et al, ). Furthermore, parturition occurring in the austral summer corresponds with direct observations made in the SRMR where pregnant bull sharks leave the feeding site in late October, returning after parturition at the beginning of the year (Brunnschweiler et al, ; Brunnschweiler & Baensch, ).…”
Section: Discussionsupporting
confidence: 86%
“…To date, information on parturition sites and nursery areas is known for only a few species. Marie, Miller, Cawich, Piovano, and Rico () confirmed the Rewa Delta as important habitat for juvenile scalloped hammerhead sharks ( Sphyrna lewini ), and Vierus et al () discovered a multispecies shark aggregation and parturition area in the Ba Estuary on the northern coast of Viti Levu. The latter study documented three juvenile bull sharks caught several kilometers upstream in the Ba River.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…As exclusively juvenile sharks were encountered, it is likely that the studied nearshore environment constitutes another parturition ground in Fiji (Brown et al., ; Cardeñosa et al., ; Marie et al., ). Size ranges of C. limbatus and S. lewini (66 ± 4 and 52 ± 5 cm, respectively) were in accordance with size ranges of neonate and young‐of‐the‐year sharks from previously published studies (Castro, ; Castillo‐Géniz, Márquez‐Farias, Rodriguez de la Cruz, Cortés, & Cid del Prado, ; Brown et al., for S. lewini ).…”
Section: Discussionmentioning
confidence: 99%
“…Using data collected from dive operators, citizen scientists and local fishermen, an increasingly clear picture of shark species abundance throughout Fiji is emerging (Brunnschweiler, Abrantes, & Barnett, 2014; Glaus, Adrian-Kalchhauser, Burkhardt-Holm, White, & Brunnschweiler, 2015;Rasalato, Maginnity, & Brunnschweiler, 2010;Ward-Paige, 2014). Specific locations with confirmed species occurrence in the scientific literature are only available for Viti Levu (Brown, Seeto, Lal, & Miller, 2016;Brunnschweiler & Earle, 2006;Cardeñosa, Glaus, & Brunnschweiler, 2017;Marie, Miller, Cawich, Piovano, & Rico, 2017) and Vanua Levu (Goetze & Fullwood, 2013), the two largest islands of Fiji. In the former case, this has led to the establishment of the Shark Reef Marine Reserve, Fiji's first national marine park, and the Fiji Shark Corridor which comprises approximately 30 miles of coastline (Brunnschweiler, 2010).…”
Section: Introductionmentioning
confidence: 99%